Soil Erosion on Mountain Trails in Eastern Iberian Peninsula - Artemi Cerdà; David Salesa; Jesús Rodrigo-Comino; Gaspar Mora-Navarro; Enric Terol; Antonio Giménez-Morera (Proceedings, 2020)
A review on trial erosion shows that soil erosion rates are one to three orders of magnitude higher than the ones recommended as sustainable. This is threatening the sustainable managements of mountain terrains, mainly in the popular hiking paths. The warm temperatures characterize Eastern Spain in winter, which results in visitors from northern Europe to walk in the coastal land mountainous terrain. This increases the pressure to the currently highly visited most popular paths. We selected representative transects of the trails of Serra de Bérnia, Puigcampana, Penyagolosa, Montcabré, Serra del Sit, Aitana, Les Tres Creus, Caroig, Cupurutxo and Circ de la Safor. All the selected study sites have Limestone parent material, and a scrubland as vegetation cover and the selected slope angle ranged in average between 5 and 10%. The surveys showed that soil erosion rates measured with a topographical method range from 13 till 450 Mg ha−1 y−1. There is a clear relation between the number of users and the damage done on the trails; and we found that short cuts are the areas that contribute with fresh sediment. Rock outcrops are found in 34% of the measured trail sections and this is a good example how the complete soil can be lost as a consequence of recreational activities.